2009
DOI: 10.1111/j.1365-2125.2009.03414.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors: problems and recommendations from a consensus meeting

Abstract: Here we discuss 15 recommendations for reducing the risks of medication errors:  1. Provision of sufficient undergraduate learning opportunities to make medical students safe prescribers.  2. Provision of opportunities for students to practise skills that help to reduce errors.  3. Education of students about common types of medication errors and how to avoid them.  4. Education of prescribers in taking accurate drug histories.  5. Assessment in medical schools of prescribing knowledge and skills and demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…Now widely implemented, electronic medication administration records (eMARs) are used to support medication management to reduce medication errors, promote patient safety and improve workflow efficiency [1][2][3]. Nurses represent the greatest numbers of eMAR users and are recognized as the "last line of defense" in preventing medication errors in acute care settings [4].…”
Section: Introductionmentioning
confidence: 99%
“…Now widely implemented, electronic medication administration records (eMARs) are used to support medication management to reduce medication errors, promote patient safety and improve workflow efficiency [1][2][3]. Nurses represent the greatest numbers of eMAR users and are recognized as the "last line of defense" in preventing medication errors in acute care settings [4].…”
Section: Introductionmentioning
confidence: 99%
“…Are these findings relevant to patient care? Medicationrelated patient safety is currently a hot topic in research, given the increase in the number of reports of the harmful effects of, often preventable, medication errors and particularly in older patients [4,22]. Investigators mention that prescribing knowledge and skills will improve if education and training are improved [4,23].…”
Section: Discussionmentioning
confidence: 99%
“…These changes have improved the clinical performance of students during and after graduation and increased student satisfaction [1,2]. However, there is also ongoing debate about the potential disadvantages of PBL, such as a loss of knowledge of basic sciences [1][2][3], and especially in pharmacology and pharmacotherapy [4]. Studies of drug safety have shown that the number of prescribing errors is high, which could adversely affect patient outcomes, leading to hospitalization or even death [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment process makes the adoption of this technology less stressful and more efficient as the staff have a better preparation. [11] Pharmacists and other pharmacy personnel also need to be able to do what they can to ensure the success of the organizations. This includes targeting at a specific system's weakness in the medicationuse processes.…”
Section: Medication Safety In Community Pharmacymentioning
confidence: 99%